Suboptimal metabolic control and decompensation in children and adolescents with diabetes mellitus type 1 - N. Ya. Filina; N. V. Bolotova; L. V. Skuchaeva (Бюллетень сибирской медицины, 2016)
Aim of the study is identifying the causes of decompensation of metabolism in children with different levels of HbA1c by studying daily glycemic profiles using a continuous monitoring system (CGMS, Medtronic MiniMed, USA).Materials and methods. Blood glucose of 207 type 1 diabetes children with different compensation level was researched by continuous glucose monitoring system (СGMS). Statistical processing of the results was carried out using XLSTATS 4.0 program.Results. The causes of diabetes suboptimal control were deficit of bolus insulin doses in 53%, «dawn phenomenon» in 23%, hidden night hypoglycemia in 26%. Patients with HbA1c level higher than 9% have deficit short acting and basal insulin that was the cause of bad metabolic control. The compare of selfcontrol results and CGMS data was preformed and pointed the importance of glucose monitoring system for decompensation causes identification.